Hidrodescloración de compuestos organoclorados empleando carburos soportados de V-Mo - De Gouveia, Ana; Pinto, Susana; Betancourt, Paulino; Brito, Joaquín; Del Toro, Raquel; González, Ismael (Ciencia, 2015)
Ver resumen PDF.